1991
DOI: 10.1002/star.19910431202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effects on the Physico‐chemical Properties of Starch from Four Cultivars of Cassava

Abstract: Four varieties of cassava plants were cultivated at CIAT in Colombia and harvested on four different occasions with a view to evaluating whether there was any relationship between the texture of the cooked roots and the constituent starch. The organoleptic qualities of the cooked roots showed considerable differences in ‘glassiness’ and hardness of texture, both between varieties and times of harvest. The starch granules were isolated and examined by a variety of techniques. The size of the granules did vary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…The starch content of flour was consistent with levels of starch in cassava root reported by both Fernandez-Quintero (1996), and Pereira and Beléia (2004). Amylose content of cassava flour was in agreement with the results reported elsewhere (Asaoka et al, 1991;Gunaratne and Hoover, 2002;Padonou et al, 2005).…”
Section: Proximate Analysissupporting
confidence: 91%
“…The starch content of flour was consistent with levels of starch in cassava root reported by both Fernandez-Quintero (1996), and Pereira and Beléia (2004). Amylose content of cassava flour was in agreement with the results reported elsewhere (Asaoka et al, 1991;Gunaratne and Hoover, 2002;Padonou et al, 2005).…”
Section: Proximate Analysissupporting
confidence: 91%
“…This may be linked to either the cultivar used or the environmental conditions of growth, which are known to in¯uence the physicochemical characteristics of cassava starch. 17,18 For both materials the gelatinisation temperature was signi®cantly higher when the fermentation was performed at 35°C, whereas the enthalpy remained unchanged. This may be due to an annealing phenomenon occurring during the long-term fermentation at 35°C as already observed for rice starch steeped in water at 40°C for 5 days.…”
Section: Proximate Analysis and Metabolite Content Of The Dried End-pmentioning
confidence: 90%
“…The fact that most of the physicochemical and functional properties did not have any correlation with the texture profile parameters indicates the influence of interaction between the various constituents. Asaoka et al 45 observed a wide variability in the texture of boiled tubers of different cassava clones but only a very small variation in the respective starch physicochemical properties, which did not have any direct correlation with texture. Apart from the physicochemical constituents, tuber texture is also influenced by cell solid content, turgor pressure of the cell, mechanical capacity of deformation of cell walls and cohesiveness provided by the cementing material of the middle lamella and also by the hydration rate of the cooked tubers.…”
Section: Texture Profile Analysismentioning
confidence: 97%